Editorial - Md. Noon, Hazizan (International Islamic University Malaysia, 2018)
As society continued to develop, it naturally transformed itself into a more complex one, making the study of it equally more challenging. Human and social sciences in particular grew out of this particular circumstance. Triggered by continuous changes, human collectivity grew from what was once a single human society into human societies which became more and more diversified as they travelled over the long journey of human history. At the core of this dynamic human movement stand a few key concepts that explain the progress of human society in its most general sense and this may be best represented by such buzzwords as development, civilisation and globalisation. ….It is against this backdrop, that this Journal finds its birth in order to participate in the contemporary discourse on various issues in these important areas of study. The Journal intends to provide an opportunity, particularly for those who are interested in the above themes to contribute with their research findings and thoughts to be shared and exchanged with other readers.